Staying Relevant and Current with Online Learning in an Increasingly Global and Competitive Environment - Lynch, Grace; James, Rhys (International Journal of Advanced Corporate Learning (iJAC), 2012)
This paper outlines the success of online learning in the workplace with corporate partners through Open Universities Australia (OUA). OUA is recognized as the national leader in online higher education in Australia with over 200,000 students studying with OUA since 1993. The corporate program helps employees formalize or extend their current skills, reach the next level in their organization or pursue relevant interests through tertiary studies. The business sector sees OUA as a highly attractive solution to fostering a culture of professional development, engagement and inclusiveness.